Ester-Based Lubricant and Anti-Leidenfrost Additive Solutions on Aluminum High-Pressure Die-Casting Applications - Nuria Cuadrado; Eduard Vidales; Manel da Silva; Wadi Wajana; Leandre Muntada; Angel Navarro; Lluis Beltran; Montserrat Vilaseca (Lubricants)
The high-pressure die-casting process is growing since it is a cost-effective solution in the production of lightweight parts for a variety of industries. Nevertheless, the harsh working conditions of the die lead to premature failing and poor quality of the produced parts. Lubricants are applied to cooling the die surface and create a protective film to minimize die wear. However, the high temperature of the die during the casting production makes it difficult for the lubricant to reach the die surface due to the Leidenfrost effect. In this study, the effectiveness of newly developed ester-based lubricants designed to address Leidenfrost phenomenon in high-pressure die-casting is evaluated at laboratory and pilot plant scale. The new lubricants are based on the same ester solution; however, one of them includes a specially formulated anti-Leidenfrost additive to optimize performance at the temperature ranges typically encountered in industrial aluminum high-pressure die-casting processes. The results show a correlation between lubricant heat-transfer capability and aluminum adhesion. Additionally, a pilot plant methodology for testing newly formulated lubricants has been established while the experimental methodology developed for assessing heat-transfer capability is validated as a rapid and cost-effective approach for evaluating lubrication alternatives for high-pressure die-casting applications. Finally, the efficiency of environmentally friendly ester-based lubricants for high-temperature applications has been demonstrated.